Trade Openness, Energy Consumption, and Financial Development Influence on Jordan’s Economy: Evidence from ARDL and Non-Granger Causality Test Approach - Fraihat, Baha Aldeen Mohammad; Al-Amarneh, Asma’a; Yaseen, Hadeel; Samarah, Miral R.; Alkhawaldeh, Bashar Younis; Buraik, Ola (International Journal of Energy Economics and Policy, 2023)
The purpose of this study is to analyze the effect of trade openness, energy consumption, and financial development on Jordan’s economic development using the Autoregressive Distributed Lag (ARDL) method. By looking at data from 1970 through 2022, the study reveals a short- and long-term impact. Short-term economic development was found to be positively influenced by energy consumption but negatively influenced by trade openness and financial development. However, financial development has a favourable effect on economic development in the long run, whereas trade openness and energy consumption have a negative effect. Furthermore, evidence of a nonlinear bidirectional causal relationship between trade openness and economic development, and evidence of a one-way causal relationship between energy consumption and economic development, were found by the results of Diks and Panchenko’s Granger causality test. The development of the economy and the financial sector also demonstrated a reciprocal causal relationship. These findings have important implications for policy and strategic planning for Jordan’s economic growth and underscore the need to carefully weigh the potential costs and gains of trade liberalization, financial sector development, and energy consumption.